Pengaruh Motivasi Belajar dan Variasi Model Pembelajaran Kooperatif terhadap Prestasi Belajar Mata Pelajaran IPS di SMPN 2 Donorojo Pacitan - Sri Iriyanti (Jurnal Penelitian Pendidikan, 2013)
Naturally, students' motivation is one of the success determinant of the learning process in the world of schooling . Therefore, the teachers are required to be more creative to keep students’ motivation in participating the learning. Cooperative learning model is one of the various existing model of the learning methods. The results showed that students learning motivation depends on the method of learning carried out by the teacher in the classroom. Practically, variety of learning methods becomes urgent to carry out, so that the learning success is achieved.